Short-lived IFN-γ effector responses, but long-lived IL-10 memory responses, to malaria in an area of low malaria endemicity - Jiraprapa Wipasa (2018)
Immunity to malaria is widely believed to wane in the absence of reinfection, but direct evidence for the presence or absence of durable immunological memory to malaria is limited. Here, we analysed malaria-specific CD4+T cell responses of individuals living in an area of low malaria transmission in northern Thailand, who had had a documented clinical attack of P. falciparum and/or P. vivax in the past 6 years. CD4+T cell effector memory (CD45RO+) IFN-γ (24 hours ex vivo restimulation) and cultured IL-10 (6 day secretion into culture supernatant) responses to malaria schizont antigens were detected only in malaria-exposed subjects and were more prominent in subjects with long-lived antibodies or memory B cells specific to malaria antigens. The number of IFN-γ-producing effector memory T cells declined significantly over the 12 months of the study, and with time since last documented malaria infection, with an estimated half life of the response of 3.3 (95% CI 1.9-10.3) years. In sharp contrast, IL-10 responses were sustained for many years after last known malaria infection with no significant decline over at least 6 years. The observations have clear implications for understanding the immunoepidemiology of naturally acquired malaria infections and for malaria vaccine development. © 2011 Wipasa et al.